Academic Rhinologists' Online Rating and Perception, Scholarly Productivity, and Industry Payments. Issue 3 (May 2021) - Goshtasbi, Khodayar; Lehrich, Brandon M.; Abouzari, Mehdi; Bazyani, Dariush; Abiri, Arash; Papagiannopoulos, Peter; Tajudeen, Bobby A.; Kuan, Edward C.
Introduction: The emergence of popular online rating websites, social media platforms, and public databases for industry payments and scholarly outputs provide a complete physician online presence which may guide choice and satisfaction. Methods: Websites of all U.S. otolaryngology academic institutions were queried for fellowship-trained rhinologists. Additional well-known and academically active rhinologists were identified by the senior author. Online ratings and comments were collected from Google, Healthgrades, Vitals, and RateMD websites, and weighted rating scores (RS) were calculated on a 1–5 scale. Results: A total of 210 rhinologists with 16 ± 9 years of practice were included, where 6901 online ratings (33 ± 47 per rhinologist) provided an average RS of 4.3 ± 0.6. RS was not different according to gender ( p = 0.58), geographic quartile ( p = 0.48), social media presence ( p = 0.41), or attending top-ranked medical school ( p = 0.86) or residency programs ( p = 0.89). Years of practice negatively correlated with RS (R = –0.22, p <0.01), and academic ranking significantly influenced RS, with professors, associate professors, and assistant professors scoring 4.1 ± 0.6, 4.3 ± 0.4, and 4.4 ± 0.6, respectively ( p = 0.03). Of the 3, 304 narrative comments analyzed (3.1 ± 11.6 per rhinologist), 76% (positive) and 7% (negative) had elements of clinical knowledge/outcomes, 56% (positive) and 7% (negative) of communication/bedside manner, and 9% (positive) and 7% (negative) of office staff, cost, and wait-time. All negative comment categories had moderate negative correlation with RS, while positive comment categories regarding knowledge/competence and bedside manner weakly correlated with higher RS. Number of publications (48 ± 54) positively correlated with 2018 industry payments (11, 384 ± 19, 025) among those receiving industry compensation >300 (n = 113). Attending a top-ranked medical school was associated with higher industry payments ( p <0.01) and H-index ( p = 0.02). Conclusion: Academic rhinologists' online RS was not associated with gender, geographic location, or attending a top-ranked training program, and their scholarly productivity was significantly correlated with total industry payments.